Effect of 1.5 MeV Proton Irradiation on Superconductivity in FeSe0.5Te0.5 Thin Films - Toshinori Ozaki; Takuya Kashihara; Itsuhiro Kakeya; Ryoya Ishigami (Quantum Beam Science, 2021)
Raising the critical current density Jc in magnetic fields is crucial to applications such as rotation machines, generators for wind turbines and magnet use in medical imaging machines. The increase in Jc has been achieved by introducing structural defects including precipitates and vacancies. Recently, a low-energy ion irradiation has been revisited as a practically feasible approach to create nanoscale defects, resulting in an increase in Jc in magnetic fields. In this paper, we report the effect of proton irradiation with 1.5 MeV on superconducting properties of iron–chalcogenide FeSe0.5Te0.5 films through the transport and magnetization measurements. The 1.5 MeV proton irradiation with 1 × 1016 p/cm2 yields the highest Jc increase, approximately 30% at 5–10 K and below 1 T without any reduction in Tc. These results indicate that 1.5 MeV proton irradiations could be a practical tool to enhance the performance of iron-based superconducting tapes under magnetic fields.